A172 ATTITUDES TOWARDS MEDICAL TREATMENT AND MEDICATION ADHERENCE IN IBD PATIENTS TAKING CONVENTIONAL, ANTI-TNF, OR COMBINATION THERAPY. (1st March 2018) - Evans, C; MacMillan, M A; Stoica, G
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic, progressive, immune-mediated disease for which Canada has among the highest incidence and prevalence in the world. Adherence to medical therapy is paramount in reaching management goals of symptom reduction and ultimately disease remission. Aims: Our aim is to illustrate the perceived necessity and concerns (attitudinal score) of IBD patients towards their medical treatment plan and patient-reported medication adherence. We hypothesize that patients' who report 'ambivalent' attitudes towards their IBD treatment are less adherent to their medical therapy compared to 'accepting' patients which could hinder treatment efficacy. Methods: We used the internationally validated 2014 ALIGN questionnaire with eligible voluntary participants from a single Canadian gastroenterology practice. Inclusion criteria was a diagnosis of IBD, current therapy of Imuran or Methotrexate, anti-TNF, or combination anti-TNF with Imuran or Methotrexate, and age ≥18 years. Results: The majority (55%) of patients were accepting of their treatment plan, 34% ambivalent, 8% skeptical, and 3% indifferent. The majority of patients were also either moderately or highly adherent to their therapy (48%, 46%), with only 6% reporting low adherence. As hypothesized, accepting patients reported higher medication adherence in comparison to ambivalent patients (49%, 39%). Conclusions: More than half of the IBD patients in our sample did not report high medication adherence, therefore their IBD is not receiving essential disease modifying therapy. Untreated IBD leaves patients at higher risk of hospitalizations, surgeries, colon cancer and reduced quality of life. Although most participants were accepting towards their current therapy, 45% felt otherwise. Patients' concerns and beliefs about their medical therapy warrant better exploration during consults as to address the effect of attitude on medication adherence and subsequent disease course. Funding Agencies: None